Allergen Challenge Chamber: an innovative solution in allergic rhinitis diagnosis - Krzych-Fałta, Edyta; Sowa, Jerzy; Wojas, Oksana; Piekarska, Barbara; Sybilski, Adam; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
The Allergen Challenge Chamber (ACC) is definitely a serious challenge on the one hand and an innovative solution in allergic rhinitis diagnosis on the other. The gradual validation of the chamber (according to the test protocol) will allow for standardisation, which is a process undertaken by centres worldwide. The process of designing a consistent system that allows for creating conditions as those in the case of natural inhalation took into account all the aspects (technical specification) necessary to ensure appropriate inhalation.